STRUKTUR DAN UNSUR KEBAHASAAN TEKS BIOGRAFI SISWA KELAS X SMA NEGERI 1 RAO - Amanda Rahmah Umayroh; Emidar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the structure (orientation, important events, and re-orientation) and linguistic elements (pronominals, material verbs, time sequence connectives, and conjunctions) in biographical texts written by tenth-grade students of SMA Negeri 1 Rao. This research employed a qualitative method with a descriptive approach. The data comprised the accuracy of structure and linguistic elements collected from biographical texts written by tenth-grade students of SMA Negeri 1 Rao in the 2025/2026 academic year. The main research instrument was the researcher (human instrument), using elicitation techniques for data collection and triangulation (cross-check) techniques for data validation. The findings reveal two key results. First, structurally, students are capable of constructing biographical texts coherently through clear orientation and depiction of important events, although the re-orientation section tends to be omitted by some students due to its optional nature. Second, linguistically, students demonstrate strong mastery in establishing chronological narrative sequences using time sequence connectives. However, further reinforcement is needed in varying material verbs and pronominals, as well as in selecting appropriate conjunctions to prevent ambiguous sentence structures.